Answer:
![(1,\ 9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/667wky5md9lzwy986j6uztrdxuzxapf9mq.png)
Explanation:
Rewrite the first equation
![-6y=-50-4x\\\\4x-6y=-50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vguu1pdyndxjn39t0rs9jmy60ne1gvp77u.png)
Now we have the following system of equations
![4x-6y=-50\\5x-6y=-49](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fbj16ayf1a1l7hidwsvl6pbgajyur11j8r.png)
To solve the system of equations multiply the first equation by -1 and add it to the second equation
![-1*4x-(-1)*6y=-50*(-1)\\\\-4x+ 6y=50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rjcg76cxggvu6go3y3kerdc110rza5ffh9.png)
![-4x+ 6y=50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qff3zphpvicwulpkaqqzunxlbyzatk0sdv.png)
+
![5x-6y=-49](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cbw0ppc9bmhtugm1xfw3alo33qfdeqa54k.png)
-----------------------------------
![x + 0 =1\\\\x=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wq7641ao75uyy6ggldxdqojboy3gq9d4so.png)
Now substitute the value of x in any of the two equations and solve for y
![5(1)-6y=-49](https://img.qammunity.org/2020/formulas/mathematics/middle-school/22myj5rxw5vu2du4yd10dvfh3641dr64uq.png)
![5-6y=-49](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yia8jk2s3gw2h0rbojmfyx2vvvsziicwx8.png)
![-6y=-49-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t6801ne2pz8byckib1tcffq2us0ujivvgb.png)
![-6y=-54](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sac0sdq7m6it40hr3ockhcbqrfqysgh4ut.png)
![y=(54)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cxeyqb96jjd58u5upq3dfz67iue68z6y3v.png)
![y=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/lbe7cetkyupszfsu17lale83fwrr9twib5.png)
The solution is:
![(1,\ 9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/667wky5md9lzwy986j6uztrdxuzxapf9mq.png)